2020
DOI: 10.1186/s12934-020-01385-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new gene expression vector for Thermus thermophilus using a silica-inducible promoter

Abstract: Background: Thermostable enzymes are commonly produced in mesophilic hosts for research and bioengineering purposes. However, these hosts do not overexpress the active forms of some biologically functional thermoenzymes. Therefore, an efficient thermophilic expression system is needed. Thermus thermophilus contains an easily manipulable genome and is therefore among the best candidate microbes for a "hot" expression system. We previously identified a strong and inducible promoter that was active in T. thermoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In some cases, thermophile protein misfolding can be removed by subunit rearrangement caused by heating of the protein . However, that is not very common and more often the problem of misfolding can be solved by using thermophiles as expression systems for thermophilic proteins can be a solution to the problem of misfolding. , These facts suggest that the protein expression system cellular environments need to be matched with those of protein source organisms in order to facilitate correct folding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, thermophile protein misfolding can be removed by subunit rearrangement caused by heating of the protein . However, that is not very common and more often the problem of misfolding can be solved by using thermophiles as expression systems for thermophilic proteins can be a solution to the problem of misfolding. , These facts suggest that the protein expression system cellular environments need to be matched with those of protein source organisms in order to facilitate correct folding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified that T. thermophilus enzyme activity is reduced when using mesophilic recombinant hosts, such as E. coli . 28 , 31 , 57 , 58 Additionally, E. coli had been previously shown to be an inadequate expression system for thermophilic proteins in functional metagenomic 59 61 and directed evolution studies. 62 64 Our results are in line with the previous findings; we also expand on them, showing how a mesophilic expression system can affect secondary structures of thermophile proteins and that the change has directionality toward less helices and more coils.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a new inducible promoter for the silica-induced protein (Sip) was used to express a thermostable β-galactosidase in T. thermophilus with a yield of 27 mg/L of culture (Fujino et al, 2016(Fujino et al, , 2020. This inducible promoter could be used in further experiments with T. thermophilus expressing the cDPG biosynthesis pathway for the industrial production of the extremolyte cDPG.…”
Section: Discussionmentioning
confidence: 99%
“…Thermus thermophilus is an ideal candidate for this purpose, as it offers fast growth rates, high cell yields, and natural competency which significantly simplifies the genetic manipulation required (Cava et al, 2009;Verdú, et al, 2019). For these reasons, a wealth of genetic tools have already been established for T. thermophilus, including plasmids (Tamakoshi et al, 1999;Moreno et al, 2003;Fujino et al, 2020), promoters (Moreno et al, 2005;Cava et al, 2009), and selection markers (Lasa et al, 1992;Nakamura et al, 2005). Several studies have already demonstrated that T. thermophilus could potentially be used as a cell factory (Doi et al, 2009;Aulitto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thermus thermophilus is a particularly suitable candidate as a production platform for thermostable proteins, given its very high natural transformation frequencies (Cava et al 2009 ; Averhoff et al 2021 ). Six inducible promoters, the P arg , P dnaK , P scs-mdh P nar , P sip , and P pilA4 promoters, have been characterized and two systems for efficient protein over-production have been reported (Moreno et al 2003 , 2005 ; Fujino et al 2020 ; Kirchner and Averhof 2023 ). However, it has to be noted that the P nar promoter is only induced under anaerobic conditions in the presence of nitrate and the P sip is only induced by addition of 10 mM silica, which leads to growth inhibition (Moreno et al 2005 ; Fujino et al 2020 ).…”
Section: Gene Discoverymentioning
confidence: 99%